2006
DOI: 10.1590/s1020-49892006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, socioeconomic status, obesity and lifestyle factors among low-income Puerto Rican women in Connecticut, U.S., 1998-1999

Abstract: The associations of acculturation and socioeconomic status with some lifestyle characteristics suggest the need for culturally appropriate programs to promote healthy lifestyle behaviors in this low-income community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…Hence, individuals with lower SES compared to those with higher SES are more likely to have poorer diet quality [43]. Fitzgerald et al [44] reported an association of low SES with less frequency of fish consumption in Puerto Rican women. Similarly, low intakes of EPA and DHA as reported in the frequency of fish consumption of 0.3 ± 0.2 times/day were found in Puerto Rican females living in poverty in Connecticut [45].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, individuals with lower SES compared to those with higher SES are more likely to have poorer diet quality [43]. Fitzgerald et al [44] reported an association of low SES with less frequency of fish consumption in Puerto Rican women. Similarly, low intakes of EPA and DHA as reported in the frequency of fish consumption of 0.3 ± 0.2 times/day were found in Puerto Rican females living in poverty in Connecticut [45].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported among Mexican-American subpopulations, using generation (first versus second generation) as a surrogate measure of acculturation 40,41 and other migrants. 42 Patterns of food intake and PA exacerbate an increase in relative body weight in migrant children. We have previously demonstrated a high prevalence of obesity and poor nutritional habits 2,25 in this population of African migrant children.…”
Section: Discussionmentioning
confidence: 99%
“…Items include for example "I often participate in my heritage cultural traditions", "I would be willing to marry a white Australian person", "I often behave in ways that are typically Australian", "It is important for me to maintain or develop the practices of my heritage culture". Participants completed the same set of questions for both their traditional and their new culture [18,21]. In line with Berry [31], acculturation patterns were determined by dividing participant responses on the VIA subscales (i.e., Iranian-orientation and Australian-orientation) into those above (high) and below (low) the mean.…”
Section: Study Measuresmentioning
confidence: 99%